EFEKTIVITAS PEMBERIAN MAKANAN TAMBAHAN (PMT) BAHAN PANGAN LOKAL UPAYA MENGURANGI TERJADINYA STUNTING PADA BALITA - Yuliana Yuliana; Lilis Lismayanti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Stunting is a common chronic nutritional problem that significantly impacts physical growth and cognitive development in children. The government's planned strategy to improve toddler nutritional intake is the provision of locally sourced food (PMT). The research method used was a systematic review, with data sources sourced from Google Scholar and the Garuda Portal. The articles selected met the inclusion criteria, with full-text articles filtered over a six-year period from 2020 to 2025. The results showed improvements in anthropometric indicators, maternal nutritional literacy, and a decrease in stunting status after PMT was administered for 30 to 90 days. Thus, PMT based on locally sourced food has been proven effective in reducing stunting in toddlers.